Enhancement in peak shifting and shaving potential of electrically heated floor residential buildings using heat extraction system. (August 2018) - Sun, Ying; Panchabikesan, Karthik; Joybari, Mahmood Mastani; Olsthoorn, Dave; Moreau, Alain; Robichaud, Miguel; Haghighat, Fariborz
Highlights: Integration of heat extraction system with EHF is proposed for peak shifting/shaving. The influence of inter-zonal airflow on model accuracy is studied. The proposed system augments the peak shifting potential of EHF by 19%. Also, potential in reduction of heating cost by 24% is explored. The proposed system will be a benefit for both the supplier and consumer. Abstract: Peak shifting plays a vital role in easing the stress on electrical grids as well as in reducing the electricity bill for consumers by taking benefit of the time-of-use tariff. In cold climates, this can be achieved effectively by storing the heat during off-peak periods and releasing it during peak periods. In this regard, electrically heated floor (EHF) with high thermal mass (e.g. bricks, concrete) can be beneficial. However, residential buildings in places like North America face practical constraints for incorporating high thermal mass on each floor. To overcome this limitation, the present work proposes a forced ventilation system or also called as heat extraction system (HES) to transfer the heat from zones that are heated by EHF with high thermal mass to zones with no such provisions. In this study, an experimental house (multistory), in which the EHF is mainly installed on the basement floor is modeled and validated using the field measurement data. The validated model is then utilized to conduct parametric analysis (effect of air flow rate and outlet location) for investigating the performance of HES and to evaluate its peak shaving potential. Simulation results show that HES increases the peak shifting potential of EHF up to 19%. On the other hand, it is also inferred that the proposed methodology increases the energy consumption by 18% but decreases the daily heating cost by 24%. It should be mentioned that the increase in energy consumption is due to the prolonged operation of the basement EHF during the off-peak period and the decrease in energy cost is because of shifting the peak to the off-peak period. The proposed concept would be a benefit to both the supplier and consumer in terms of peak shifting and heating cost saving.